Chemical and sensory stability of fried-salted peanuts flavored with oregano essential oil and olive oil - Olmedo, Rubén Horacio (2009)
Synthetic antioxidants, such as BHA, BHT and PG are used in many foods to prevent rancidity. However, their health safety is questioned. There is renewed interest in the increased use of naturally occurring antioxidants like essential oils from aromatic plants. The objective of this work was to evaluate the effect of oregano essential oil and olive oil on the oxidative stability of fried-salted peanuts. RESULTS: Fried-salted peanuts (FP), fried-salted peanuts with oregano essential oil (FP-O) and fried-salted peanuts with oregano essential oil and olive oil (FP-OO) were prepared. Peroxide value (PV), p-anisidine value (AV) and conjugated diene (CD) measurements, and descriptive analysis were analyzed on the products during 112 days of storage. FP-OO showed higher stability during storage. PV and AV at the end of storage were lower in FP-OO (57.70 ? 7.77, respectively) followed by FP-O (63.94 ? 8.30) and FP (76.38 ? 9.33, respectively). The oxidized and cardboard flavour intensities increased more in FP during storage than the other products while the roasted peanutty flavour also decreased more in FP. CONCLUSION: Oregano essential oil and olive oil showed protective effect against lipid oxidation in fried-salted peanuts increasing the shelf-life of this product.